Strategies for Sustainable Growth and Decent Work in the Platform Economy - Sfetcu, Lucian (Technium Social Sciences Journal, 2024)
Achieving Sustainable Development Goal 8 (SDG 8) is imperative for promoting global prosperity and social equity. This article explores the multifaceted challenges and opportunities associated with fostering sustainable, inclusive, and enduring economic growth, full and productive employment, and decent work for all—particularly in the context of platform economies and temporary employment. By synthesizing recent literature and integrating economic and labour market theories, we examine how technological advancements influence economic productivity and job creation. We also address ethical concerns and potential inequalities arising from these technologies if not managed responsibly. Strategies such as upskilling initiatives, portable benefits, worker cooperatives, and ethical AI development are discussed as means to mitigate these challenges. The article underscores the need for a comprehensive and collaborative approach involving policymakers, platform operators, and stakeholders to achieve the objectives of SDG 8.